The Application of Crude Ginger Protease as an Inhibitive Assay for Heavy Metals (Journal of Environmental Microbiology and Toxicology, 2019)
In this work, a novel source of protease for the bioassay of heavy metals has been developed using proteases extracted from ginger. The result shows that the optimum protease activity was reached at 1 mg/mL protein concentration of the ginger protease. The optimum casein concentration toward crude ginger protease activity was 1.75 mg/mL. The most suitable pH for protease from crude ginger protease was within the range from pH 5.0 to 7.0. The proteases exhibited high protease activity in a broad range of temperature from 20 to 60 oC. The optimum incubation time for the enzyme occurred at minute 30. Among the six heavy metals tested, only three heavy metals inhibited proteolytic activity of ginger crude with an inhibition more than 30% at 1 mg/L. The calculated LC50 for mercury, copper and silver were, 0.182, (95%, confidence interval (C.I.) 0.134 to 0.283), 0.071, (95% C.I. of 0.056 to 0.096), 0.054, (95% C.I. of 0.039 to 0.085), respectively. Data on the sensitivity of various proteases to heavy metals shows that the crude ginger protease is comparable in sensitivity for mercury to the achromopeptidase, bromelain, papain assays. The crude ginger protease assay for copper is comparable in sensitivity to the papain assay and appears to be more sensitive than the rest of the assays. For silver, the ginger protease was the most sensitive while other assay methods are either unable or be able to detect higher concentration of silver. The crude proteases extracted from ginger showed a good potential for the development of a rapid, sensitive, and economic inhibitive assay for the biomonitoring of mercury, copper, and silver in the environment.
Keywords: inhibitive assay; ginger protease; heavy metals; Coomassie assay; mercury